Enhancement of Thermal Resistance by Metal Ions in Thermotolerant Zymomonas mobilis TISTR 548 - Kosaka, Tomoyuki; Nishioka, Aya; Sakurada, Tomoko; Miura, Kento; Anggarini, Sakunda; Yamada, Mamoru (Frontiers in Microbiology, 2020)
The thermal resistance of fermenting microbes is a key characteristic of stable fermentation at high temperatures. Therefore, the effects of various metal ions on the growth of Zymomonas mobilis TISTR 548, a thermotolerant ethanologenic bacterium, at a critical high temperature (CHT) were examined. Addition of Mg2+ and K+ increased CHT by 1°C, but the effects of the addition of Mn2+, Ni2+, Co2+, Al3+, Fe3+, and Zn2+ on CHT were negligible. To understand the physiological functions associated with the addition of Mg2+ or K+, cell morphology, intracellular reactive oxygen species (ROS) level, and ethanol productivity were investigated at 39°C (i.e., above CHT). Cell elongation was repressed by Mg2+, but not by K+. Addition of both metals reduced intracellular ROS level, with only K+ showing the highest reduction strength, followed by both metals and only Mg2+. Additionally, ethanol productivity was recovered with the addition of both metals. Moreover, the addition of Mg2+ or K+ at a non-permissive temperature in 26 thermosensitive, single gene-disrupted mutants of Z. mobilis TISTR 548 revealed that several mutants showed metal ion-specific growth improvement. Remarkably, K+ repressed growth of two mutants. These results suggest that K+ and Mg2+ enhance cell growth at CHT via different mechanisms, which involve the maintenance of low intracellular ROS levels.